Adding liraglutide to diet and exercise to maintain weight loss – is it worth it?. (4th March 2022) - Doggrell, Sheila A.
ABSTRACT: Introduction: Obesity is a major risk factor for cardiovascular disease, diabetes, osteoarthritis, and some cancers. Weight loss is an obvious management for this, but a major problem is that after weight loss, many people regain weight. Areas Covered: In the following evaluation of S-LITE (NCT04122716, Combined effects of GLP-1 analogue and exercise on maintenance of weight loss after very-low calorie diet), the author gives emphasis to the prevention of weight regain by liraglutide, not the effects of exercise. In S-LITE, liraglutide (with or without exercise) was effective in reducing weight regain in subjects with obesity. Expert opinion: The subjects with obesity in S-LITE were limited by the enrollment criteria, and the findings of S-LITE cannot be generalized. The increased heart rate with liraglutide did not occur when liraglutide was combined with exercise, and this suggests that liraglutide should probably not be used alone, but only with exercise to maintain weight loss. As the only presently available medicine to have been shown to be effective against weight regain, liraglutide should probably be preferred to other weight-loss medicines in this circumstance. However, without clear evidence that liraglutide treatment for obesity prevents diabetes and/or reduces cardiovascular risk, it is difficult to justify using it.